2019
DOI: 10.3390/ijerph16234635
|View full text |Cite
|
Sign up to set email alerts
|

Personal Factors, Internet Characteristics, and Environmental Factors Contributing to Adolescent Internet Addiction: A Public Health Perspective

Abstract: Individual characteristics, family- and school-related variables, and environmental variables have equal importance in understanding Internet addiction. Most previous studies on Internet addiction have focused on individual factors; those that considered environmental influence typically only examined the proximal environment. Effective prevention and intervention of Internet addiction require a framework that integrates individual- and environmental-level factors. This study examined the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 53 publications
3
57
0
8
Order By: Relevance
“…Environmental risk factors such as accessibility and industry-driven marketing factors may also serve an important role in developing IGD. It has been found that higher exposure to internet game advertisements increases the risk for internet game addiction among a representative sample of Korean youths [8]. Possession of easily accessible digital devices or a lack of parental rules concerning gaming behavior has been suggested as factors that influence the development of gaming disorder [6].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental risk factors such as accessibility and industry-driven marketing factors may also serve an important role in developing IGD. It has been found that higher exposure to internet game advertisements increases the risk for internet game addiction among a representative sample of Korean youths [8]. Possession of easily accessible digital devices or a lack of parental rules concerning gaming behavior has been suggested as factors that influence the development of gaming disorder [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies conducted in China (Wang et al, 2013), Hong Kong (Wang et al, 2014), Japan (Mihara et al, 2016), Korea (Chung et al, 2019), Spain (Tejeiro Salguero & Moran, 2002), and the United States (Gentile et al, 2009), 8% to 16% of adolescents are identified as having a gaming addiction (World Health Organization [WHO], 2018a). This complex phenomenon has various unique aspects, including psychological (e.g., personality, life satisfaction, past psychological maltreatment, loneliness), social (e.g., socioeconomic, family, learning environments, cyberPsycho effects), and cultural (e.g., differences in government, ethnicity, and culture; Bozoglan, 2018;Young, 2017) factors.…”
mentioning
confidence: 99%
“…Students were asked to select one response option to a 5-point Likert scale from "not at all" to "always". The scores for all 20 items were summed (therefore from 20 to 100), and a total score of 50 or beyond meant a presence of the Internet addiction behavior [12,28]. The reliability and validity of YIAT-C have been established in Chinese children [12], and in the present study, the Cronbach's alpha was 0.921.…”
Section: Internet Addictionmentioning
confidence: 63%